Diagnostic accuracy of liver stiffness measurement and serum hyaluronic acid for detecting liver fibrosis in chronic hepatitis B with respect to ALT levels - Prachya Kongtawelert (2018)
Background: The assessment of liver fibrosis in chronic hepatitis B is crucial in clinical practice. Objective: We compared the diagnostic accuracy of liver stiffness measurement (LSM) using transient elastography and serum hyaluronic acid (HA) in detecting liver fibrosis (METAVIR) in chronic hepatitis B, with respect to ALT levels. Method: One hundred fifty-six Thai patients with chronic hepatitis B who had undergone a liver biopsy were enrolled, and included 112 (71.8%) men and 44 (28.2%) women. The mean age of the patients was 40.1±12.2 years. The predictive accuracy was analyzed by comparing the areas under the receiver-operating characteristic curves (AUROCs). Result: LSM was superior to HA in predicting fibrosis stages of ≥F2 (AUROCs were 0.820 vs 0.727, p=0.009), ≥ F3 (0.910 vs 0.848, p=0.015) and F4 (0.938 vs 0.876, p=0.031). There was significant correlation between ALT level and LSM value, while such correlation between ALT and HA was not detected. Regarding the subgroup of patients with ALT levels >80 IU/L (2 × ULN), AUROCs of LSM and HA for predicting fibrosis stages of ≥F2 (0.733 vs 0.696), ≥F3 (0.892 vs 0.844) and F4 (0.934 vs 0.893) were not significantly different. Conclusion: LSM was superior to HA in predicting liver fibrosis and cirrhosis in patients with chronic hepatitis B. However, in patients with ALT elevation, the diagnostic performance of LSM was reduced and its accuracy was comparable to that of HA. Thus, HA could be an alternative method in assessing liver fibrosis in patients with high ALT levels.